PENGARUH PERSEPSI APARAT ATAS STRATEGI INTENSIFIKASI DAN EKSTENSIFIKASI PAJAK DAN RETRIBUSI DAERAH TERHADAP PENINGKATAN PENDAPATAN ASLI DAERAH (PAD) DI PROVINSI JAWA BARAT (WILAYAH 1 BOGOR) - Junaedi Siswanto (Nusa Putra University, 2019)
This research was conducted at Revenue, Local Finance and Asset Revenue and Management Agency (DPPKADs) in Province of West Java (Bogor Region 1), intended to obtain empirical evidences about the influence of personal’s perception of local tax and retribution intensification and extensification on tehe increase of locally Raised Revenues (Pendapatan Asli Daerah-PAD) in Province of West Java (Bogor Region 1). The major research data collection was by questionnaire with analysis unit of DPPKADs in 6 (six) towns/regencies in Bogor Region 1 and the respondence were eselons 2,3, and 4 officers of 150 in total. The secondary data was obtained by studying documents existing in 6 (six) DPPKADs. Data processing used Multiple Reression Analysis. The simultaneous test result showed that personal’s perception of local tax and retribution intensification and extensification simultanousely has positive, significant influence on the increase of PAD in Province of West Java (Bogor Region 1). The results of partial test showed that: local tax and retribution intensification on the increase of PAD in Province of West Java (Bogor Region 1) and local tax and retribution extensification on the increase of PAD in Province of West Java (Bogor Region 1).